Combining energy efficiency with self-cleaning properties in smart glass functionalized with multilayered semiconductors. (1st November 2020) - Garlisi, Corrado; Trepci, Esra; Al Sakkaf, Reem; Azar, Elie; Palmisano, Giovanni
Abstract: We propose here a new approach based on a combined study of the self-cleaning and energy-efficiency properties of stratified WO3 /Cu–TiO2 coatings for glazing applications. The multifunctional performance was investigated by varying the number of layers deposited on the glass substrate (i.e., 1, 2, 4 layers), while energy efficiency was assessed using building energy modeling. Results indicate that the self-cleaning ability can be boosted by a multilayer configuration due to the inhibited charge recombination and to a gradual rise in surface roughness and porosity with the increasing number of layers. In particular, the highest wettability and degradation of toluene under simulated solar light were achieved over the coating consisting of Cu-doped TiO2 stacked with WO3 in a 4-layer configuration. On the other hand, the analogous sample, but in the 2-layer configuration, was the most active sample in the oxidation of carbon monoxide. In terms of energy efficiency, the applied coatings led to important energy savings, exceeding 8% in total energy consumption and 18% in cooling loads. The best energy efficiency levels in the tested glazing configurations were achieved with single-layer WO3 . However, its low visible transmittance reduced the amount of natural daylight entering the studied buildings, unintentionally increasing the electric lighting loads. The results highlight the importance of alternative configurations, such as Cu-doped TiO2 in a dual-layer arrangement with WO3, which provide a better balance between energy efficiency and access to daylight, an important driver of occupant comfort and wellbeing. Highlights: Combined study of the self-cleaning and energy-efficiency properties of stratified coatings. Carbon monoxide and toluene were successfully degraded. The energy efficiency of the functionalized glass was studied using building energy modeling. The applied coatings led to energy savings exceeding 8% in total energy consumption and 18% in cooling loads.